A modular systems biological modelling framework studies cyclic nucleotide signaling in platelets. (7th October 2022) - Breitenbach, Tim; Englert, Nils; Osmanoglu, Özge; Rukoyatkina, Natalia; Wangorsch, Gaby; Heinze, Katrin; Friebe, Andreas; Butt, Elke; Feil, Robert; Dittrich, Marcus; Gambaryan, Stepan; Dandekar, Thomas
Highlights: Platelet modelling is achieved via decomposition into sub models using a standardized framework. Our bilinear framework considers mass action and control theory for optimal dosage. Combination of sub models allows systematic analysis of model performance. Flexible model assembling allows to easy adapt for specific scenarios, e.g. therapy. Framework is validated with cGMP data and VASP phosphorylation. Abstract: Background: The cyclic nucleotides cAMP and cGMP inhibit platelet activation. Different platelet signaling modules work together. We develop here a modelling framework to integrate different signaling modules and apply it to platelets. Results: We introduce a novel standardized bilinear coupling mechanism allowing sub model debugging and standardization of coupling with optimal data driven modelling by methods from optimization. Besides cAMP signaling our model considers specific cGMP effects including external stimuli by drugs. Moreover, the output of the cGMP module serves as input for a modular model of VASP phosphorylation and for the activity of cAMP and cGMP pathways in platelets. Experimental data driven modeling allows us to design models with quantitative output. We use the condensed information about involved regulation and system responses for modeling drug effects and obtaining optimal experimental settings. Stepwise further validation of our model is given by direct experimental data. Conclusions: We present a general framework for model integration using modules and their stimulus responses. We demonstrate it by a multi-modular model for platelet signaling focusing on cGMP and VASP phosphorylation. Moreover, this allows to estimate drug action on any of the inhibitory cyclic nucleotide pathways (cGMP, cAMP) and is supported by experimental data.